2021
DOI: 10.1002/eap.2317
|View full text |Cite
|
Sign up to set email alerts
|

Strong impact of management regimes on rhizome biomass across Central European temperate grasslands

Abstract: Grassland ecosystems account for approximately 40% of terrestrial biomes globally. These communities are characterized by a large allocation to belowground biomass, often exceeding its aboveground counterpart. However, this biomass investment cannot be entirely attributed to the acquisitive function of roots. Grassland plants also allocate to non-acquisitive, stem-derived, belowground organs, such as rhizomes. These organs are responsible for the key plant functions of space occupancy, resprouting after damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…In that study, below-and above-ground biomass scaled linearly (Ottaviani et al (2021), similar to the positive linear relation between corm size and spring biomass production in H. hemerocallidea (Fig. 3).…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In that study, below-and above-ground biomass scaled linearly (Ottaviani et al (2021), similar to the positive linear relation between corm size and spring biomass production in H. hemerocallidea (Fig. 3).…”
Section: Discussionsupporting
confidence: 77%
“…The most marked impact of single season of clipping on H. hemerocallidea was the loss of more than half of its corm mass. Ottaviani et al (2021) also observed far lower (by > 70%) rhizome biomass in temperate grassland mown twice versus grassland mown once annually.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations